2001
DOI: 10.1002/joc.637
|View full text |Cite
|
Sign up to set email alerts
|

The role of eastern North Pacific tropical storms in the rainfall climatology of western Mexico

Abstract: This paper explores the role that tropical storms (TS) of the eastern North Pacific play in the rainfall climatology of western Mexico. It uses an 18-station rainfall grid, along with a data base of storm tracks (1949 -1997). TS rainfall is defined by a distance threshold, so that for each station in the grid, daily rainfall recorded when a TS is located within 550 km of the station is considered as TS-derived; rainfall recorded in the absence of a TS or when a storm is beyond 550 km from a station is by defau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
129
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(137 citation statements)
references
References 24 publications
5
129
0
3
Order By: Relevance
“…The Niño3 index was chosen to represent ENSO variability for this study, rather than other ENSO indices based on regions farther west, because it represents equatorial Pacific SST variability directly south of the Mexican coast affected by tropical cyclones. Previous analyses of ENSO and rainfall variability (e.g., Gershunov and Barnett, 1998;Englehart and Douglas, 2001;Gutzler et al, 2002) have found a distinct change in statistics of interannual variability before and after 1977, when Pacific Ocean SSTs and the atmospheric circulation shifted in association with the PDO (Graham, 1994;Mantua et al, 1997). We therefore examine relationships between SST and tropical cyclone counts for separate periods before and after 1977.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…The Niño3 index was chosen to represent ENSO variability for this study, rather than other ENSO indices based on regions farther west, because it represents equatorial Pacific SST variability directly south of the Mexican coast affected by tropical cyclones. Previous analyses of ENSO and rainfall variability (e.g., Gershunov and Barnett, 1998;Englehart and Douglas, 2001;Gutzler et al, 2002) have found a distinct change in statistics of interannual variability before and after 1977, when Pacific Ocean SSTs and the atmospheric circulation shifted in association with the PDO (Graham, 1994;Mantua et al, 1997). We therefore examine relationships between SST and tropical cyclone counts for separate periods before and after 1977.…”
Section: Methodsmentioning
confidence: 96%
“…This distance was selected based on previous research (Englehart and Douglas, 2001) showing that tropical cyclones within this distance from the coast were likely to generate observable precipitation at coastal stations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous regional-scale analyses have also been done to relate rainfall variability to changes in atmospheric circulation (e.g. Brito-Castillo et al, 2002), tropical cyclone activity (Englehart and Douglas, 2001), and the El Niño-southern oscillation (ENSO) signal (e.g. Reyes and Mejía-Trejo, 1991;Douglas and Englehart, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The selected divisional locations reflect considerations of data availability -access to records from fairly consistent reporting stations over the period 1943-2006 -and the desire to sample a diverse set of climatological rainfall regimes within Mexico. The analysis purposely excludes more coastal locations where previous work indicates that tropical cyclone (TC) activity contributes significantly to warm-season rainfall regimes (Englehart and Douglas, 2001;Douglas and Englehart, 2002).…”
Section: Introductionmentioning
confidence: 99%